Ordered mesoporous crystalline aluminas from self-assembly of ABC triblock terpolymer–butanol–alumina sols1. Issue 61 (4th July 2015) - Tan, Kwan Wee; Sai, Hiroaki; Robbins, Spencer W.; Werner, Jörg G.; Hoheisel, Tobias N.; Hesse, Sarah A.; Beaucage, Peter A.; DiSalvo, Francis J.; Gruner, Sol M.; Murtagh, Martin; Wiesner, Ulrich
<x xml:space="preserve">Abstract</x> One-pot synthesis of periodically mesostructured γ-alumina using an ABC triblock terpolymer as structure-directing agent and in situ derived rigid carbon scaffold.